Influence of Organic Derivatives on Direct Regeneration of finger millet genotype CO 9 - Babu, G. Atul; Ravindhran, R. (International Journal of Scientific Research in Biological Sciences, 2019)
Finger millet (Eleusine coracana (L.) Gaertn.) is a commercially important food crop extensively cultivated in the arid and semi-arid tropical regions of India and East Africa. The current study was designed to develop an efficient protocol for micropropagation by the influence of additives to enhance the number of shoots per explant from Shoot Apical Meristems (SAMs) of finger millet genotype CO 9. The highest shoot regeneration frequency (95.89%) with an average of 46.52 shoots per explant and 10.86 cm shoot length per explant was achieved when SAMs were cultured in Shoot Regeneration Medium (SRM) containing Murashige and Skoog’s (MS) medium supplemented with 3.0 mg/L 6-Benzyl Amino Purine (BAP), 2.0 mg/L Kinetin and 5% coconut water, 300 mg/L proline and 400 mg/L casein enzymatic hydrolysate, and 3 mg/L glycine. Sub-culturing the SAMs in SRM at 2 weeks interval for 8 weeks resulted in an increase in the number of shoots per explant. The highest rooting frequency (100%) with an average root length of 7.32 cm was obtained on full-strength MS medium supplemented with 0.25 mg/L IAA. and successfully acclimated in the field, subsequently developed into fertile plants. Thus, the procedure described is a rapid and consistent method useful for efficient large-scale propagation and genetic transformation in finger millet.